Public transport supply and demand for UP campus - Apilado, Jonard A.; Regidor, Jose Regin F.; Perez, Kathleen G.; Napalang, Maria Sheilah; Montalbo, Cresencio (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
The main objective of the study is to estimate the supply and demand of public transport of the six routes in UP Campus and to detennine if the existing transport system is enough to meet the demand. Data collection will generate primary and secondary data to estimate passenger demand and current levels of public transport supply with UP Diliman and immediate environs as study area. The following are the major surveys undertaken: Boarding and Alighting Survey, License Plate Survey and On-board OD Survey. Route Measured Capacity was used in calculating required number of units of PUJ for the served demand. A sensitivity analysis was performed to consider the unserved demand which is asstuned as a percentage of the total demand. OD Table and Desire Lines were used to determine the passengers' trip pattern. Results showed that there is relatively enough supply that meets the demand for the UP Diliman Campus. It is also observed that the trip pattem of the passengers is unique per route since they have different course. They only have overlaps inside the campus. The trip pairs or heavier demand can be observed to the nearby zones of the route's service lines. It is highly recommended to acquire data and perform sensitivity analysis for one whole day for better estimation of the served demand. It is also recommended that the number of operating jeepney units plying inside the campus be retained as its existing number and any proposals for additional units should be further analyzed.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Transportation -- University of the Philippines; Transportation -- Passenger traffic